Bentuk Ritual Budaya Jeknek Sappara (Mandi Safar) Di Desa Balangloe Taroang, Kabupaten Jeneponto: Tinjauan Semiotik: Form of Ritual Culture of Jeknek Sappara (Mandi Safar) in Balangloe Village, Taroang, Jeneponto District: Semiotic Review - Indarwati Indarwati; Lina Mariana (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Jeknek Sappara's cultural customs are traditionized by the Balangloe Taroang community and are believed to bring blessings. This research will focus on the form of rituals in traditional cultural ceremonies. This type of research is a qualitative research with the theme of local culture. Data were collected by observation method, with recording, recording and interview techniques. Data were analyzed using descriptive-qualitative analysis. The results of the study show that there are several forms of ritual in this traditional ceremony, namely: 1) Appasempa; 2) A’lili; 3) Patoeng; 4) A’rurung Kalompoang; 5) Dengka Pada; 6) Pakarena; 7) Paolle; 8) Pabbatte; 9) A’Jeknek; 10) Akraga; dan 11) Manyukkang.